Menopause and the influence of culture: another gap for Indigenous Australian women? - Jones, Emma; Jurgenson, Janelle; Katzenellenbogen, Judith; Thompson, Sandra (Biomed Central Ltd., 2012)
Background: There is great variation in experience of menopause in women around the world. The purpose of this study was to review current understanding of Australian Aboriginal and Torres Strait Islander (Indigenous) women’s experiences of menopause. The literature pertaining to the perception, significance and experience of menopause from a number of cultural groups around the world has been included to provide context for why Indigenous women’s experience might be important for their health and differ from that reported in other studies of Australian women and menopause. Methods: A search of databases including Ovid Medline, Pubmed, Web of Science, AUSThealth, AMED, EMBASE, Global Health and PsychINFO was undertaken from January 2011 to April 2011 using the search terms menopause, Indigenous, Aboriginal, attitudes, and perceptions and repeated in September 2012. Results: Considerable research shows significant variation across cultures in the menopausal experience. Biological, psychological, social and cultural factors are associated with either positive or negative attitudes, perceptions or experiences of menopause in various cultures. Comparative international literature shows that neither biological nor social factors alone are sufficient to explain the variation in experiences of the menopausal transition. However, a strong influence of culture on the menopause experience can be found. The variation in women’s experience of menopause indicates that different cultural groups of women may have different understandings and needs during the menopausal transition. While considerable literature exists for Australian women as a whole, there has been little investigation of Australian Indigenous women, with only two research studies related to Indigenous women’s experiences of menopause identified.Conclusions: Differences in biocultural experience of menopause around the world suggest the importance of biocultural research. For the Indigenous women of Australia, the relative contribution of culture, social disadvantage and poor general health compared with non-Indigenous women to the experience of menopause is unknown. As such, further research and understanding of the experience of Indigenous women around Australia is needed. This information could assist individuals, families, cultural groups and healthcare providers to enhance management and support for Indigenous Australian women.